Tritium activity levels in drinking water of Adana, Turkey - Gören E.; Turhan S.; Ugur F.A.; Gezer F.; Özdemir B.; Ufuktepe Y. (Springer Science and Business Media LLC, 2014)
Tritium activity in potable drinking water samples from Adana city were measured using liquid scintillation counting after distillation procedure. The results exposed that the activity concentrations of the tritium measured in one-third of these samples were lower than minimum detectable activity which has a value of 2 Bq/L for counting time of 1,500 min. However, the maximum and mean value of the tritium activity was found to be 9.1 Bq/L (77.3 TU) and 7.0 Bq/l (59.4 TU), respectively. These values were substantially below the 100 Bq/L which is normative limit in Turkey for waters intended for human consumption. The highest values of annual effective dose received by infants, children and adults due to measured tritium activity were estimated as 0.041, 0.057 and 0.120 μSv/y, respectively.
Keywords: Liquid scintillation counting; Drinking water; Adana (Turkey); Tritium; Annual effective dose; 2. Zero hunger; 13. Climate action; 6. Clean water